Bi-Stable Perception: Self-Coordinating Brain Regions to Make-Up the Mind - Devia, Christ; Concha-Miranda, Miguel; Rodríguez, Eugenio (Frontiers in Neuroscience, 2022)
Bi-stable perception is a strong instance of cognitive self-organization, providing a research model for how ‘the brain makes up its mind’. The complexity of perceptual bistability prevents a simple attribution of functions to areas, because many cognitive processes, recruiting multiple brain regions, are simultaneously involved. The fMRI evidence suggests the activation of a large network of distant brain areas. Concurrently, EEG/MEG literature shows sub second oscillatory activity and phase synchrony on several frequency bands. Strongly represented are beta and gamma bands, often associated with neural/cognitive integration processes. The spatial extension and short duration of brain activities suggests the need for a fast, large-scale neural coordination mechanism. To address the range of temporo-spatial scales involved, we systematize the current knowledge from mathematical models, cognitive sciences and neuroscience at large, from single-cell- to system-level research, including evidence from human and non-human primates. Surprisingly, despite evidence spanning through different organization levels, models, and experimental approaches, the scarcity of integrative studies is evident. In a final section of the review we dwell on the reasons behind such scarcity and on the need of integration in order to achieve a real understanding of the complexities underlying bistable perception processes.